The Legal Protection for The Use of A Notary's Right of Refusal in Investigations - Irda Nur Khumaeroh; Agus Prasetia Wiranto; M. Rizal Bagaskoro (JURNAL AKTA, 2024)
One of the responsibilities of a notary in carrying out his position in accordance with his obligations and promises of office is to keep everything about the deed he makes confidential. This writing, thus, aims to find out and analyze the procedures for using the rights and obligations of refusal by notaries in investigative examinations and the forms of legal protection for notaries who are examined in the criminal justice process. This research employed normative legal research methods emphasizing document study or library research. A normative juridical approach was carried out by reviewing and studying library materials in the form of statutory regulations relating to the problem under study. The notary's right of refusal applies relatively in the sense that if there are more specific rules that invalidate the right of refusal, the notary cannot exercise his right of refusal. The form of legal protection for notaries who are examined in the criminal justice process is contained in the UUJN (Act on Notary Position), in Article 66, stating that in carrying out a summons, law enforcement officials must request permission from the Notary Honorary Council. Legal protection, according to the Notary Honorary Council, is to supervise and inspect notaries so that they continue to walk the right path in accordance with the law; when a notary is summoned in a criminal case, the Notary Honorary Council has the authority to allow it to be examined or not.